2007
DOI: 10.1097/chi.0b013e31803065b5
|View full text |Cite
|
Sign up to set email alerts
|

Child, Family, School and Community Risk Factors for Poor Mental Health in Brazilian Schoolchildren

Abstract: Objective: To identify risk factors for poor child mental health in the south-eastern Brazilian municipality of Taubaté Method: In 2001 we carried out a representative school-based survey of Brazilian schoolchildren aged 7-14 years (response rate 83%). We collected extensive data on child mental health and on potential risk and protective factors at baseline (N=1112) and collected follow-up information on mental health outcome after three years (N=760). We used the Strengths and Difficulties Questionnaire as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
1
16

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 19 publications
3
33
1
16
Order By: Relevance
“…The continued adverse effects of parental stress on child psychopathology have been documented previously in the literature (45)(46)(47)(48). It is possible that other adverse circumstances that have been found to contribute to maternal stress (e.g., socioeconomic…”
Section: /36mentioning
confidence: 88%
“…The continued adverse effects of parental stress on child psychopathology have been documented previously in the literature (45)(46)(47)(48). It is possible that other adverse circumstances that have been found to contribute to maternal stress (e.g., socioeconomic…”
Section: /36mentioning
confidence: 88%
“…Os fatores de risco e proteção analisados neste estudo foram baseados em dados da literatura (Fleitlich-Bilyk & Goodman, 2001;A. Goodman et al, 2007;Koller & Lisboa, 2007;Poletto, Koller, & Dell'Aglio, 2009;Rutter, 1987;Werner, 1989) e reafi rmados pelos profi ssionais dos Serviços Especializados.…”
Section: Instrumentosunclassified
“…Alguns apontam possíveis associações entre vivenciar situações de maus tratos na infância e juventude aos riscos que elas possam representar para o desenvolvimento de transtornos mentais, em cuja ocorrência, verifi ca-se o aparecimento de sinais e sintomas de ordem emocional como resposta do sujeito aos estressores físicos e psicossociais. O estudo dessas possíveis associações tem sido de grande importância para as pesquisas em psicopatologia (Assis et al, 2009;FleitlichBilyk & Goodman, 2001;A. Goodman, Fleitlich-Bilyk, Patel, & Goodman, 2007;Paula et al, 2008;Polanczyk, Zavaschi, Benetti, Zenker, & Gammerman, 2003;Serafi m, Saffi , Achá, & Barros, 2011 (Assis et al, 2009).…”
unclassified
“…Other study procedures, such as having female interviewers working in privacy at the health centre, rather than conducting in-home interviews that could be overheard by family members, may have minimized reporting bias. A previous study reported on risk factors for child mental health problems in Brazil with multivariate analysis 6,22 . Conducted in the city of Taubaté, south-eastern Brazil, the study used a stratified probabilistic sample of students from public (urban and rural) and private (all urban) schools (n = 1251; attrition rate: 17%).…”
Section: Special Theme -Childhood Injuries and Violence Physical Punimentioning
confidence: 99%
“…Conducted in the city of Taubaté, south-eastern Brazil, the study used a stratified probabilistic sample of students from public (urban and rural) and private (all urban) schools (n = 1251; attrition rate: 17%). 22 A screening instrument (Strengths and Difficulties Questionnaire) was also used to identify emotional (or internalizing) problems and behavioural (or externalizing) problems. Parent, teacher and youth reports were combined to identify clinical cases.…”
Section: Special Theme -Childhood Injuries and Violence Physical Punimentioning
confidence: 99%